The Chloroplast Permease PIC1 Regulates Plant Growth and Development by Directing Homeostasis and Transport of Iron(1)([W]) - Duy, Daniela (American Society of Plant Biologists, 2011)
The membrane-spanning protein PIC1 (for permease in chloroplasts 1) in Arabidopsis (Arabidopsis thaliana) was previously described to mediate iron transport across the inner envelope membrane of chloroplasts. The albino phenotype of pic1 knockout mutants was reminiscent of iron-deficiency symptoms and characterized by severely impaired plastid development and plant growth. In addition, plants lacking PIC1 showed a striking increase in chloroplast ferritin clusters, which function in protection from oxidative stress by sequestering highly reactive free iron in their spherical protein shell. In contrast, PIC1-overexpressing lines (PIC1ox) in this study rather resembled ferritin loss-of-function plants. PIC1ox plants suffered from oxidative stress and leaf chlorosis, most likely originating from iron overload in chloroplasts. Later during growth, plants were characterized by reduced biomass as well as severely defective flower and seed development. As a result of PIC1 protein increase in the inner envelope membrane of plastids, flower tissue showed elevated levels of iron, while the content of other transition metals (copper, zinc, manganese) remained unchanged. Seeds, however, specifically revealed iron deficiency, suggesting that PIC1 overexpression sequestered iron in flower plastids, thereby becoming unavailable for seed iron loading. In addition, expression of genes associated with metal transport and homeostasis as well as photosynthesis was deregulated in PIC1ox plants. Thus, PIC1 function in plastid iron transport is closely linked to ferritin and plastid iron homeostasis. In consequence, PIC1 is crucial for balancing plant iron metabolism in general, thereby regulating plant growth and in particular fruit development.